Prototype Rancang Bangun Robot Penyiram Tanaman Otomatis Dengan Kendali Fuzzy - Akmal Ekaprasetyo; Wahyu Setyo Pambudi (Jurnal Ilmiah Matrik, 2020)
Robot is a mechanical device that can perform physical tasks, both with human supervision and control (semi-automatic), or with a program that has been defined in advance (artificial intelligence). Robots are usually used for heavy tasks, repetitive and monotonous work such as cleaning up toxic wastes, underwater and space exploration, mining, search and rescue, and in agriculture. The agricultural robot designed is a four-wheeled mobile robot that can water plants automatically by taking into account the temperature and soil humidity. This agricultural robot design uses line follower system (line follower robot) and wireless communication through ESP8266. The robot detects the temperature and soil humidity through LM35 and YL-69 sensors which are readable through ATmega32 microcontroller programmed by C programming language.